2019
DOI: 10.2298/gensr1901031f
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance and stability of seed, protein and oil yields of seven soybean cultivars determined in field experiments in Slovenia

Abstract: The environment can have a crucial influence on soybean production in particular regions, even more so when production environments are different from breeding environments. Therefore, soybean cultivars must be evaluated in field trials at various locations in order to explore the duration of the growing period and capacity of yield, which is based on interactions between genotype and environment. Seven soybean cultivars originating from five European countries were evaluated for thousand-see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…KOBAREI et al (2011), reported 43-44% reduction in soybean yield under stressful conditions compared to normal conditions. Similar results were reported by FLAJŠMAN et al (2019).…”
Section: Methodssupporting
confidence: 92%
“…KOBAREI et al (2011), reported 43-44% reduction in soybean yield under stressful conditions compared to normal conditions. Similar results were reported by FLAJŠMAN et al (2019).…”
Section: Methodssupporting
confidence: 92%
“…Correlation analysis of some chosen traits showed different interdependence between measured variables depending on the environment. The results of this study pointed out that among the seven tested varieties, ES Mentor, NS Mercury and NS Favorit were best genotypes (FLAJŠMAN et al, 2019).…”
Section: Correlations Of Examined Traitsmentioning
confidence: 69%
“…Therefore, soybean varieties must be evaluated in field trials at various locations in order to explore the duration of the growing period and capacity of yield, which is based on interactions between genotype and environment. Results of FLAJŠMAN et al (2019) showed that variety and environment had a significant impact on all measured variables. In almost all tested environments the best varieties were ES Mentor (3425-5628 kg seed/ha) and NS Mercury (3468-5342 kg seed ha -1 ).…”
Section: Correlations Of Examined Traitsmentioning
confidence: 98%
See 2 more Smart Citations